The Golden Index: A classification system for player performance in football attacking plays - Pereira, T.; Ribeiro, J.; Grilo, F.; Barreira, D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
In this study, a formula called the Golden Index was developed that calculates a value for each player according to their individual and collective performances. This method identifies the most important players, designated as Golden Players, in football attacking plays. This study was organized in two main phases: (1) selection, definition and validation, including weighting assignment, of a set of variables associated with players` performance through application of statistical techniques to uniformize variables values that compose the Golden Index formula and (2) applicability of the Golden Index formula to quantify players` performance of Club Atlético de Madrid over 2016-2017 season. A questionnaire was given to football experts in order to validate and determine the weight of each of the 12 variables selected. Descriptive statistics with standardization techniques were used to set the weights and uniformize each variable of the Golden Index formula. Applying the Golden Index formula to Club Atlético de Madrid 2016-2017 season named Koke, Yannick Carrasco and Filipe Luís as the Golden Players, while the centre-backs Lucas Hernández, Stefan Savic and Diego Godín and striker Fernando Torres received negative indexes. Results suggested that the Golden Index formula is a valuable and useful tool in capturing the individual and collective performance of players in attacking play in football.